Application of the Student Facilitator and Explaining Learning Model to Improve Student Learning Outcomes in Basic Competencies Applying Concepts and Rules Types of Lines in Technical Drawings at SMK Negeri 1 Lotu for the 2022/2023 Academic Year - Carlos Yogi Moanoita Telaumbanua; Yelisman Zebua; Aprianus Telaumbanua (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The problem in this study is that the Student Facilitator and Explaining learning model has not been optimally applied to the Basic Competence of Applying Concepts and Rules of Types of Lines in Technical Drawings and student learning outcomes are only limited to achieving KKM, namely 70. Research objectives: (1) To describe the learning process by using apply the Student Facilitator and Explaining learning model to the Basic Competency of Applying Concepts and Rules of Types of Lines in Technical Drawings at SMK Negeri 1 Lotu for the 2022/2023 Academic Year, and (2) To find out student learning outcomes in the Basic Competency of Applying Type Concepts and Rules -Types of Lines in Technical Drawings at SMK Negeri 1 Lotu for the 2022/2023 Academic Year. This type of research is Classroom Action Research (CAR). This research was conducted at SMK Negeri 1 Lotu with research subjects of class X DPIB, totaling 22 people. The instruments in this study were observation sheets of the learning process (teacher respondents), student activity observation sheets, photo documentation, and student practical activity tests. Research results: (1) In cycle I (First) the average percentage of observations in the learning process (teacher respondents) is 62.50%, the average percentage of observations of student activity is 53.13%, the average learning outcomes is 65.07 with a percentage of student completeness of 45% and this result has not reached the target that has been set, namely 70. (2) While in cycle II (two) the average percentage of observations in the learning process (teacher respondents) is 85.71%, the average – the average percentage of observations of student activity is 82.10%, the average calculated student learning outcomes is 82.99 which is categorized as good with a complete percentage of student learning outcomes of 100% and has reached the set target of 70. From the research findings above it can be concluded that by applying the Student Facilitator and Explaining learning model to the subject of Technical Drawing Basic Competency Applying Concepts and Rules of Types of Lines in Technical Drawings and can improve student learning outcomes at SMK Negeri 1 Lotu.